2019
DOI: 10.1007/s11630-019-1069-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Multistage Centrifugal Pump Used in an Organic Rankine Cycle (ORC) System under Various Condensation Conditions

Abstract: In an Organic Rankine cycle (ORC) system, the working fluid pump plays an important role in the system performance. This paper focused on the operating characteristics of a multistage centrifugal pump at various speed and condensation conditions. The experimental investigation was carried out to assess the influence of the performance of the pump by the ORC system with special attention to actual net power output, thermal efficiency as well as back work ratio (BWR). The results showed that an increase in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Compared with the expander and heat exchanger, researches on electricity driven pump (EDP) for ORC is quite scare. Few related studies discussed the multistage centrifugal pump or gear pump which showed that the working efficiency had a remarkable influence on the system performance of ORC [23,24]. However, in some research cases, the pump work is often selectively ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the expander and heat exchanger, researches on electricity driven pump (EDP) for ORC is quite scare. Few related studies discussed the multistage centrifugal pump or gear pump which showed that the working efficiency had a remarkable influence on the system performance of ORC [23,24]. However, in some research cases, the pump work is often selectively ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In small scale ORC applications, pumps power consumption can severely affect the thermal efficiency and the net power output of the ORC system [30]. However, as pump efficiency is often very low [31], its improved off-design performance can play a key role in the reduction of the back work ratio [32]. Moreover, the cavitation problem can occur in off-design conditions and an overcharging of the working fluid is usually done, leading also to an improvement of the isentropic efficiency of the machine [33].…”
Section: Introductionmentioning
confidence: 99%